The Effect of Shame and Shame Memories on Paranoid Ideation and Social Anxiety - Matos, Marcela (2013)
Social wariness and anxiety can take different forms. Paranoid anxiety focuses on the malevolence of others, whereas social anxiety focuses on the inadequacies in the self in competing for social position and social acceptance. This study investigates whether shame and shame memories are differently associated with paranoid and social anxieties.